Characterisation of genomic and mitochondrial genes of the tunicate, Pyura stolonifera - Crafford, Tania (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical Sciences)) -- University of Stellenbosch, 1993.